Health risk assessment of Ubeji Creek residents' exposure to BTEX from consumption of locally sourced foods. Issue 1 (1st January 2021) - Asejeje, Gbolahan Iyiola; Ipeaiyeda, Ayodele Rotimi; Onianwa, Percy Chuks
ABSTRACT: Ubeji Creek in Niger Delta Region of Nigeria suffers environmental pollution attributable to petroleum exploration. Therefore, this study was undertaken to investigate BTEX (benzene, toluene, ethylbenzene, and xylene) levels in locally sourced staple foods and dietary BTEX exposure of residents of the Creek from consumption of these foods. Fish, shrimps, pawpaw, cassava, pineapple, and bitter leaf were collected quarterly in a year at designated sampling locations along the creek. The food samples were collected, processed and analysed for BTEX using gas chromatography-flame ionisation detection. Dietary exposure assessment for the Ubeji Creek residents due to BTEX in the foods was conducted based on food consumption data from a food frequency questionnaire survey completed by 530 residents. Mean, maximum, and percentiles BTEX dietary exposures were estimated by both probabilistic and deterministic analyses methods using the @RISK® software through a first-order Monte Carlo simulation at 50, 000 iterations. The food samples contained BTEX levels with pineapple tissue having the highest concentration (1.35 ± 0.11 mg/kg). Fish and shrimps have the highest consumption rates of about 120 g/person/day and 90 g/person/day, respectively. The deterministic and probabilistic assessments indicated that fish and shrimps were the highest contributors to the intakes of total BTEX compared to other foods. The deterministic and probabilistic analyses of dietary intakes of benzene revealed that total dietary intakes of benzene exceeded benzene oral reference dose (RfDo), minimum risk level (MRL), and maximum permissible risk (MPR) level. This indicates that the residents who consume the studied foods are potentially at risk of BTEX dietary exposure.